Hydrophobic MOF material-based mixed matrix membrane and preparation method thereof

By adopting a mixed matrix flat film based on hydrophobic MOF materials in the membrane separation technology, and using the impregnation and lifting process, the "trade-off" effect between selectivity and permeability in the prior art and the scale limitations of the membrane preparation process are solved, and efficient butanol separation is achieved.

CN119680403AActive Publication Date: 2025-03-25NINGBO UNIV +1

Patent Information

Application Number
CN202411952040.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-25
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing membrane separation technology has a "trade-off" effect between selectivity and permeability in the separation process of butanol, and the traditional spin coating process limits the effective area and separation efficiency of the film, making it difficult to achieve large-scale production.

Method used

A mixed matrix flat film based on hydrophobic MOF material is used to load it onto a flat carrier through an impregnation and lifting process, and combined with specific cast film liquid ratios and process parameters, a film with high selectivity and high permeability is prepared.

Benefits of technology

It achieves the improvement of the permeability of the membrane while ensuring high selectivity, expands the effective area of ​​the membrane, is suitable for industrial-scale production, and shows good performance in butanol separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005215087540000011
    Figure HDA0005215087540000011
  • Figure HDA0005215087540000012
    Figure HDA0005215087540000012
  • Figure HDA0005215087540000021
    Figure HDA0005215087540000021
Patent Text Reader

Abstract

The invention discloses a hydrophobic MOF material-based mixed matrix flat sheet membrane and a preparation method and application thereof.The preparation method comprises the following steps: S1, weighing an MOF material and a cross-linking agent, adding the weighed MOF material and cross-linking agent into a solvent, and fully and uniformly mixing to obtain a solution A; s2, weighing an organic polymer, adding a solvent, and fully and uniformly mixing to obtain a solution B; s3, preparing a membrane casting solution: mixing the solution A and the solution B, fully and uniformly mixing, adding a catalyst, and uniformly mixing to obtain the membrane casting solution; and S4, mounting a flat plate support body on a pulling machine, loading the membrane casting solution on the flat plate support body by adopting a dip-coating process, and then drying to obtain the mixed matrix flat plate membrane. The dipping, extracting and film-drawing process has the advantages of wide applicability, simplicity and convenience in operation, controllable film thickness, uniformity and transparency of the film and low energy consumption, the prepared film is uniform, the area of the film is larger, and the permeability of the film can be improved while high selectivity of the mixed matrix film is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane separation, and in particular to a mixed matrix membrane based on hydrophobic MOF materials and a preparation method thereof. Background Art

[0002] Butanol is a representative product with excellent performance in biofuels. Compared with ethanol, it has higher calorific value, lower corrosiveness, lower vapor pressure, weaker hygroscopicity, and better compatibility with gasoline, so it can be stored and used more conveniently. Biomass fermentation is one of the important ways to prepare butanol, but there is a product inhibition effect, which cannot obtain a high yield, and the alcohol concentration is low (generally less than 5%), making it difficult to separate and recover subsequent products.

[0003] Membrane separation has the advantages of no phase change, small footprint, high efficiency, energy saving and environmental protection, etc. It has been widely studied and applied in the field of water environment and gas separation. Membrane separation technology uses materials with selective separation function and the selective separation of membranes to achieve the separation of different components of the feed liquid. Among them, pervaporation (PV) is a kind of membrane separation technology, especially suitable for the separation of azeotropes. PV uses the chemical potential difference of a certain component upstream and downstream of the feed liquid membrane as the driving force to achieve mass transfer, and uses the difference in affinity and mass transfer resistance of the membrane to different components in the feed liquid to achieve selectivity. The most widely used aspects are: recovery of organic matter in water, separation of organic and organic mixed systems, and dehydration of organic solvents. Pervaporation technology uses the vapor pressure difference of the components on both sides of the membrane as the driving force for mass transfer, and separates the mixture based on the "dissolution-diffusion" or "adsorption-separation" mechanism. The material of the membrane determines the performance of the membrane. By selecting the membrane material and adjusting the membrane structure, the separation effect of the membrane can be improved and the cost and energy consumption of the separation process can be reduced. Therefore, the controllable preparation of membrane materials with high-efficiency separation performance can reduce the cost of bio-butanol, increase the production capacity of butanol, and help achieve my country's dual carbon goals.

[0004] In past studies, pure organic membranes were often used to enrich butanol at low concentrations, but pure organic membranes all have a "trade-off" effect, that is, the selectivity and permeability of the membrane will increase and decrease. In order to break the "trade-off" effect, scholars introduced porous inorganic fillers into the organic matrix to obtain a mixed matrix membrane, which can further improve the permeability of the membrane while ensuring high selectivity.

[0005] For mixed matrix membranes, the selection of inorganic fillers is crucial. MOF materials (Metal-Organic Framework) are crystalline materials assembled by metal ions and organic ligands. Therefore, MOF materials have the advantages of both inorganic and organic substances. There are abundant organic groups on their surface, which are compatible with organic membrane materials and can better avoid the interface defects of mixed matrix membranes. Compared with traditional porous materials, MOFs have huge specific surface area and porosity. At the same time, MOF materials have diverse topological structures, and because of the rich variety and modifiability of metals and ligands, they can achieve selective adsorption and separation of guest molecules of different sizes, polarities, and functional groups.

[0006] In the pervaporation membrane assembly, the membrane layer with separation function is synthesized on the support. Depending on the type of membrane assembly, the support has different shapes, such as tubular support, flat support, disc support; common support materials include α-Al2O3 support, γ-Al2O3 support, PAN support, PVDF support, etc. A flat membrane is required in the plate-and-frame pervaporation membrane assembly, and the flat membrane layer with separation function is synthesized on the flat support. At present, the preparation processes of flat membranes include: vacuum filtration method, hot drop method, spraying method, spin coating method, etc. At present, most of the flat membranes reported are to load the casting liquid onto a single surface of the α-Al2O3 disc support by spin coating. This process can only grow a membrane on one surface of the support, and cannot grow a membrane on the other surface. Therefore, the surface area of ​​the separation membrane is small and the working efficiency is low. Since spin coating is only effective for coatings of small-area supports, it is not suitable for large-scale production, which also limits its application in research and development and large-scale production. Summary of the invention

[0007] The purpose of the present invention is to provide a mixed matrix membrane based on hydrophobic MOF materials and a preparation method thereof in view of the above problems.

[0008] In order to achieve its purpose, the present invention adopts the following technical solution:

[0009] The first aspect of the present invention provides a method for preparing a hydrophobic MOF material mixed matrix flat membrane, comprising the following steps:

[0010] S1. Prepare liquid A: weigh MOF material and cross-linking agent, add them into solvent, mix them thoroughly, and obtain liquid A;

[0011] S2. Prepare liquid B: weigh the organic polymer, add the solvent, and mix thoroughly to obtain liquid B;

[0012] S3, preparing a casting solution: mixing liquid A with liquid B, mixing them thoroughly and evenly, adding a catalyst, and mixing them evenly to obtain a casting solution;

[0013] S4. Preparation of mixed matrix flat membrane

[0014] The flat support is installed on a lifting machine, and the casting liquid is loaded onto the flat support by an immersion lifting process, and then dried to obtain a mixed matrix flat membrane.

[0015] The solvent is selected from one or more of methanol, ethanol, isooctane, n-heptane, and cyclohexane, preferably isooctane;

[0016] The MOF material is selected from ZIF-8, ZIF-L, ZIF-67, ZIF-90, ZIF-7, and ZIF-71, preferably ZIF-8, and preferably the particle size of ZIF-8 is 10 to 120 nm or 14 to 50 nm;

[0017] The organic polymer is selected from polymethylphenylsiloxane (PMPS), polydimethylsiloxane (PDMS), polyether block amide (PEBA), preferably polymethylphenylsiloxane (PMPS);

[0018] The cross-linking agent is selected from tetraethyl orthosilicate (TEOS), methyl orthosilicate (TMOS), methyltrimethoxysilane (MTMS), preferably tetraethyl orthosilicate (TEOS);

[0019] The catalyst is selected from dibutyltin dilaurate (DBTDL), dimethylcyclohexylamine (DMCHA), N,N-dimethylbenzylamine (DMBA), triethylenediamine (TEDA), preferably dibutyltin dilaurate (DBTDL);

[0020] The flat support is selected from one of an α-Al2O3 carrier, a γ-Al2O3 carrier, a PAN carrier, and a PVDF carrier, and is preferably an α-Al2O3 carrier.

[0021] The mass ratio of the catalyst, the cross-linking agent, the organic polymer, the MOF material and the solvent in the casting solution in step S3 is 1:(8-12):(90-110):(5-20):(300-1000), preferably 1:(8-12):(90-110):(5-16):(600-1000) or 1:(9-11):(95-105):(10-15):(800-1000) or 1:10:100:15:800;

[0022] In step S4, the viscosity of the casting solution is 40 cP to 65 cP or 40 cP to 50 cP.

[0023] Preferably, step S1 specifically comprises: first weighing the MOF material and adding it to the solvent (preferably by ultrasonic stirring and mixing) to prepare a MOF dispersion, adding a crosslinking agent and a solvent to the MOF dispersion, and mixing them thoroughly to obtain a liquid A; preferably, after adding the crosslinking agent and the solvent to the MOF dispersion, ultrasonic mixing and magnetic stirring are used for mixing;

[0024] Preferably, probe ultrasound is used, with an amplitude of 30% to 90% and a duration of 1 to 5 minutes, more preferably an amplitude of 60% and a duration of 5 minutes;

[0025] The stirring rate of the magnetic stirring is 200-600 rpm, and the stirring time is 0.5-1 h, preferably the stirring rate is 600 rpm, and the stirring time is 1 h.

[0026] Preferably, in step S2, the organic polymer is weighed and added to the solvent, and magnetic stirring is performed to mix the mixture thoroughly to obtain liquid B;

[0027] The stirring rate of the magnetic stirring is 200-600 rpm, and the stirring time is 0.5-1 h, preferably the stirring rate is 600 rpm, and the stirring time is 1 h.

[0028] Preferably, in step S3, liquid A and liquid B are mixed, and ultrasonic and magnetic stirring are used to fully mix them, and then a catalyst is added and mixed to obtain a casting liquid;

[0029] Preferably, probe ultrasound is used, with an amplitude of 30% to 90% and a duration of 1 to 5 minutes, more preferably an amplitude of 60% and a duration of 5 minutes;

[0030] The stirring rate of the magnetic stirring is 200-600 rpm, and the stirring time is 0.5-1 h, preferably the stirring rate is 600 rpm, and the stirring time is 1 h.

[0031] In step S4, the immersion and pulling process is as follows: the support body is immersed in the casting liquid at a speed of 60 to 200 mm min -1 (Preferably 100~180mm min -1 Or 150~180mm min -1 ), the residence time is 5 to 30 s (preferably 5 to 25 s or 5 to 20 s or 5 to 10 s), and then the support is pulled out from the casting liquid at a pulling speed of 60 to 200 mm min -1 (Preferably 100-180 mmmin -1 Or 150~180mm min -1 ), the dipping-pulling operation is performed once or twice (preferably once); further preferably, the speed at which the support is immersed in the casting solution is 180 mm min-1 The residence time is 10s, and then the support is pulled out from the casting liquid at a pulling speed of 60mm min -1 ;

[0032] The drying comprises air-drying the support with the casting liquid adhered to the surface and then drying it; preferably, drying at room temperature for 12 to 24 hours, then drying with air at 80 to 120°C for 6 to 12 hours, and finally drying in a vacuum at 80 to 120°C for 6 to 12 hours; further preferably, drying at room temperature for 24 hours, drying with air at 100°C for 12 hours, and drying in a vacuum at 100°C for 12 hours.

[0033] The second aspect of the present invention provides a mixed matrix flat membrane based on a hydrophobic MOF material, which is prepared by any of the preparation methods described above.

[0034] The third aspect of the present invention provides the use of the above-mentioned mixed matrix flat membrane based on hydrophobic MOF materials in the enrichment of alcohols.

[0035] Preferably, in the above-mentioned application technical solution, the mixed matrix flat membrane is used in the pervaporation technology to separate and enrich alcohols; the alcohols include n-butanol, isobutanol, n-propanol, isopropanol and ethanol;

[0036] Preferably, the alcohol is n-butanol with a concentration of 0.1 to 3 wt % and an enrichment temperature of 40 to 80°C.

[0037] The beneficial effects of the present invention are:

[0038] The current disc-shaped flat membrane can only grow on one side and the effective membrane area is small, the separation efficiency is low, and due to the limitation of the preparation process, there is a lot of waste of casting liquid and the process cannot be scaled up. The immersion pulling membrane making process adopted by the present invention has the following advantages: 1. Wide applicability: The immersion pulling method is suitable for the continuous preparation of large-size membrane layers on solid surfaces with complex geometric structures and chemical properties. 2. Easy to operate: This method is simple to operate and easy to mechanize, and is suitable for uniform coating of large-area and complex-shaped supports. 3. Controllable film thickness: By adjusting process parameters such as solution concentration, immersion time, pulling speed, etc., the thickness and performance of the membrane can be controlled. 4. Uniformity and transparency: The film thickness is controlled between tens of nanometers and several microns, with good uniformity and transparency. 5. Low energy consumption: This method can be operated at room temperature, with simple operation, short preparation time and low energy consumption. The present invention finally obtains the process of the present invention through a large amount of preliminary research such as selection of casting liquid raw materials, selection of casting liquid raw material ratio, process selection, and exploration of process parameters. The prepared mixed matrix flat membrane has a uniform membrane layer and a larger membrane area. It is verified by amplification experiments that the membrane still has good performance after amplification and meets the requirements of large-scale production.

[0039] Through a large number of experimental explorations, the present invention finally determined that the MOF material is mixed and hybridized with an organic polymer, and then loaded onto a flat carrier through an impregnation and pulling process, which is assembled into a membrane component for pervaporation and alcohol permeation, which can improve the permeability of the membrane while ensuring the high selectivity of the mixed matrix membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 These are the results of the effects of different ZIF-8 particle sizes on the pervaporation performance of ZIF-8 / PMPS mixed matrix membranes.

[0041] Figure 2 These are the results of the effect of ZIF-8 loading amount on the pervaporation performance of ZIF-8 / PMPS mixed matrix membrane.

[0042] Figure 3 The results show the effect of casting solution viscosity on the pervaporation performance of ZIF-8 / PMPS mixed matrix membrane.

[0043] Figure 4 Graph showing the pervaporation performance of ZIF-8 / PMPS mixed matrix membrane (ZIF-8 loading is 13 wt.%) at different operating temperatures.

[0044] Figure 5 This is the pervaporation performance diagram of ZIF-8 / PMPS mixed matrix membrane (ZIF-8 loading is 13wt.%) under different n-butanol / water system concentrations.

[0045] Figure 6 This is a graph showing the long-term stability test results of ZIF-8 / PMPS mixed matrix membrane (ZIF-8 loading is 13 wt.%) for pervaporation of 1 wt.% n-butanol / water system at 40°C.

[0046] Figure 1-6 The specifications of the mixed matrix membrane are length×width of 3 cm×3 cm and thickness of 6 mm. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.

[0048] The experimental methods in the following examples are conventional methods unless otherwise specified.

[0049] Example 1 Effects of different parameters on the performance of mixed matrix flat membranes

[0050] 1. Preparation method of mixed matrix flat membrane based on MOF materials

[0051] A method for preparing a mixed matrix flat membrane based on MOF materials is performed according to the following steps (taking the preparation of a mixed matrix flat membrane with a ZIF-8 loading of 13 wt.% as an example):

[0052] S1. Preparation of Solution A:

[0053] 0.75 g ZIF-8 was added to 14.25 g isooctane (CAS No.: 540-84-1) to prepare a ZIF-8 dispersion. 0.5 g crosslinking agent TEOS (tetraethyl orthosilicate, CAS No.: 562-90-3) and 5.75 g isooctane were added to the ZIF-8 dispersion and mixed by probe ultrasonic in an ice-water bath under the ultrasonic conditions of 60% probe ultrasonic amplitude and 5 min; then magnetic stirring was performed under the conditions of 600 rpm and 1 h to obtain liquid A.

[0054] S2. Preparation of Solution B:

[0055] Take 5 g of organic PMPS (polymethylphenylsiloxane, CAS No.: 9004-73-3) and add it to 20 g of isooctane. Mix well under magnetic stirring at a stirring speed of 600 rpm for 1 h to obtain liquid B.

[0056] S3. Preparation of casting solution

[0057] Pour liquid A into liquid B, and mix the mixed solution by probe ultrasonic mixing in an ice-water bath. The ultrasonic conditions are: probe ultrasonic amplitude: 60%, ultrasonic time: 5min, and then magnetic stirring. The magnetic stirring conditions are: speed: 600rpm, stirring time: 1h. Then add catalyst DBTDL (dibutyltin dilaurate, CAS No.: 77-58-7) and stir evenly (magnetic stirring conditions are: speed: 400rpm, stirring time: 10s) to form a uniform and stable casting solution.

[0058] S4. Preparation of mixed matrix flat membrane

[0059] Pour the casting liquid into the casting liquid tank, fix the fully cleaned and dried α-Al2O3 flat plate support (length × width 3cm × 3cm, thickness 6mm) to the automatic lifting machine through the membrane assembly, and adjust the speed of the support body immersing in the casting liquid (viscosity 40cP ~ 50cP) to 180mm min -1 The residence time is 10s, and then the support is pulled out from the casting liquid at a pulling speed of 60mm min -1 The support with the casting solution adhered to the surface was placed at room temperature of 25°C to dry for 24 hours, then placed in a forced air drying oven at 100°C for 12 hours, and finally placed in a vacuum drying oven at 100°C for 12 hours to obtain a ZIF-8 / PMPS mixed matrix flat membrane with stable performance.

[0060] 2. Investigating the effects of different MOF materials on flat membranes

[0061] In this experiment, the following MOF materials were used to prepare MOF-PMPS mixed matrix membranes according to the method in the previous "one": ZIF-8 (2-methylimidazole zinc salt, CAS number: 59061-53-9), ZIF-L, and ZIF-67 (2-methylimidazole cobalt salt, CAS number: 46201-07-4).

[0062] The mass ratio of catalyst / cross-linking agent / PMPS / MOF material / solvent in the casting solution is: 1:10:100:15:800.

[0063] The prepared mixed matrix membrane was placed in a raw material liquid pool and subjected to pervaporation test in a 1wt.% n-butanol solution at 40°C. The results are shown in Table 1. When the MOF material was selected as ZIF-8, the pervaporation flux of the synthesized ZIF-8 / PMPS mixed matrix flat membrane reached 925.86 gm -2 h -1 , the n-BuOH / H2O separation factor reached 37.65, which was higher than that of ZIF-L / PMPS and ZIF-67 / PMPS mixed matrix flat membranes, indicating that ZIF-8 / PMPS has better butanol separation effect than mixed matrix membranes synthesized by other MOF materials.

[0064] Table 1

[0065] Mixed matrix membrane <![CDATA[Flux (gm -2 h -1 )]]> <![CDATA[n-BuOH / H2O separation factor]]> ZIF-8 / PMPS mixed matrix membrane 925.86 37.65 ZIF-L / PMPS mixed matrix membrane 871.05 24.07 ZIF-67 / PMPS mixed matrix membrane 580.06 18.56

[0066] 3. Investigating the effect of different ZIF-8 particle sizes on the membrane

[0067] ZIF-8 / PMPS mixed matrix membrane was prepared using ZIF-8 of different particle sizes (14 nm, 50 nm, 120 nm) according to the method in the previous "one". The mass ratio of catalyst / cross-linker / PMPS / ZIF-8 / solvent in the casting solution was 1:10:100:15:800 (i.e., the ZIF-8 loading was 13.0 wt.%).

[0068] The prepared mixed matrix membrane was subjected to pervaporation test in a 1 wt.% n-butanol / water solution at 40°C. The results are shown in FIG. Figure 1 As shown: 14nm-ZIF-8 / PMPS mixed matrix membrane has the best separation effect, with a pervaporation flux of 925.86gm -2 h -1, n-BuOH / H2O separation factor reached 37.65, and it had better pervaporation performance than 50nm-ZIF-8 / PMPS mixed matrix membrane and 120nm-ZIF-8 / PMPS mixed matrix membrane synthesized by incorporating larger particle size ZIF-8, indicating that smaller particle size ZIF-8 nanoparticles have better compatibility with PMPS matrix. The subsequent research will focus on 14nm-ZIF-8 / PMPS mixed matrix membrane.

[0069] 4. Investigating the effect of ZIF-8 particle loading on the membrane

[0070] The casting solutions with different 14nm-ZIF-8 loadings were prepared by referring to the method in the previous "1": 14nm-ZIF-8 / PMPS mixed matrix membranes with 14nm-ZIF-8 loadings of 0wt.%, 4.8wt.%, 9.1wt.%, 13.0wt.% and 16.7wt.% were prepared respectively. The ZIF-8 loading was calculated by the mass of the raw materials ZIF-8 and PMPS used:

[0071] ZIF-8 loading amount = mass of ZIF-8 / (sum of the mass of ZIF-8+PMPS)

[0072] The mass ratios of catalyst / cross-linker / PMPS / ZIF-8 / solvent in the casting solution of 14nm-ZIF-8 / PMPS mixed matrix membranes with 14nm-ZIF-8 loadings of 0wt.%, 4.8wt.%, 9.1wt.%, 13.0wt.% and 16.7wt.% are 1:10:100:0:800, 1:10:100:5:800, 1:10:100:10:800, 1:10:100:15:800 and 1:10:100:20:800, respectively.

[0073] The prepared mixed matrix membrane was subjected to pervaporation test in a 1 wt.% n-butanol / water solution at 40°C. The results are shown in FIG. Figure 2 As shown: The separation effect of the 14nm-ZIF-8 / PMPS mixed matrix membrane with a loading of 13wt.% was the best, and the pervaporation flux reached 925.86gm -2 h -1, n-BuOH / H2O separation factor reached 37.65. Before the loading of 13.0wt.%, the pervaporation performance of the mixed matrix membrane gradually increased. After the loading of 13.0wt.%, the n-BuOH / H2O separation factor in the pervaporation process dropped sharply at a loading of 16.7wt.%, indicating that excessive loading produces non-selective space, resulting in a significant increase in flux and a significant decrease in selectivity. In the future, the 14nm-ZIF-8 / PMPS mixed matrix membrane with a loading of 13wt.% will be the main target for research.

[0074] 5. Investigate the influence of viscosity of casting liquid on the film

[0075] Referring to the method in the previous "one", a 14nm-ZIF-8 / PMPS mixed matrix membrane with a loading of 13wt.% was prepared. Since the viscosity of the casting solution will continue to increase with time, pulling under casting solutions of different viscosities will produce mixed matrix membranes of different film thicknesses, thereby affecting the final pervaporation performance of the mixed matrix membrane. Therefore, a viscometer is used to accurately detect the target viscosity of the casting solution, and the pulling operation is performed when the target viscosity is reached.

[0076] The mixed matrix membranes pulled at different viscosities were subjected to pervaporation tests in a 1 wt.% n-butanol / water solution at 40°C. The results are shown in FIG. Figure 3 As shown: The mixed matrix membrane synthesized when the casting solution viscosity is 45cP has good pervaporation performance, and the pervaporation flux reaches 744.06gm -2 h -1 , the n-BuOH / H2O separation factor reached 38.03. At the same time, the pervaporation performance of the mixed matrix membrane synthesized when the casting solution viscosity was 40cP and 50cP was also at a high level. As the casting solution viscosity continued to increase, the pervaporation performance of the mixed matrix membrane began to decline. It can be seen that the optimal casting solution viscosity range for pulling is 40cP~50cP. In the future, the main goal of the research will be to pull the synthesized mixed matrix membrane within the casting solution viscosity range of 40cP~50cP.

[0077] 6. Investigate the influence of casting liquid raw material ratio on the membrane

[0078] Referring to the method in the previous "a", casting solutions with different isooctane dosages were prepared: 14nm-ZIF-8 / PMPS mixed matrix membranes with mass ratios of catalyst / crosslinking agent / organic polymer / ZIF-8 / solvent in the casting solution of 1:10:100:15:600, 1:10:100:15:800, and 1:10:100:15:1000 were prepared respectively. The prepared mixed matrix membranes were subjected to pervaporation test in a 1wt.% n-butanol / water solution at 40°C, and the results are shown in Table 2:

[0079] Table 2

[0080] Product Number Ratio of raw materials for casting liquid <![CDATA[Flux (gm -2 h -1 )]]> <![CDATA[n-BuOH / H2O separation factor]]> A1 1:10:100:15:600 545.34 28.12 A2 1:10:100:15:800 925.86 37.65 A3 1:10:100:15:1000 773.25 23.17

[0081] From the results in Table 2, it can be seen that when the casting solution raw material ratio is 1:10:100:15:800, the synthesized ZIF-8 / PMPS mixed matrix membrane has the highest pervaporation performance.

[0082] 7. Investigate the influence of residence time on membrane during pulling process

[0083] Referring to the method in the previous "a", 14 nm-ZIF-8 / PMPS mixed matrix membranes (ZIF-8 loading of 13.0 wt.%) with different residence times in the casting solution during the pulling process were prepared. The mass ratio of catalyst / crosslinker / polymer / ZIF-8 / solvent in the casting solution was: 1:10:100:15:800, and the immersion speed was: 180 mm min -1 , pulling speed: 60mm min -1 The prepared mixed matrix membrane was subjected to pervaporation test in a 1 wt.% n-butanol / water solution at 40°C. The results are shown in Table 3:

[0084] Table 3

[0085] Product Number Dwell time during the lifting process <![CDATA[Flux (gm -2 h -1 )]]> <![CDATA[n-BuOH / H2O separation factor]]> B1 5s 1239.45 17.87 B2 10s 925.86 37.65 B3 20s 672.67 28.03

[0086] From the results in Table 3, it can be seen that when the residence time of the flat support in the casting solution during the pulling process is 10 s, the synthesized ZIF-8 / PMPS mixed matrix membrane has the highest pervaporation performance.

[0087] 8. Investigate the influence of immersion speed / pulling speed on the membrane during the pulling process

[0088] According to the method in the previous "a", a 14nm-ZIF-8 / PMPS mixed matrix membrane with a loading of 13.0wt.% at different immersion speeds / pulling speeds in the casting solution during the pulling process was prepared. The mass ratio of catalyst / crosslinking agent / polymer / ZIF-8 / solvent in the casting solution was: 1:10:100:15:800, and the residence time in the casting solution was: 10s. The prepared mixed matrix membrane was subjected to pervaporation test in a 1wt.% n-butanol / water solution at 40°C, and the results are shown in Table 4:

[0089] Table 4

[0090] Product Number Immersion speed / pulling speed <![CDATA[Flux (gm -2 h -1 )]]> <![CDATA[n-BuOH / H2O separation factor]]> C1 <![CDATA[180mmmin -1 / 180mmmin -1 ]]> 1023.87 21.23 C2 <![CDATA[180mmmin -1 / 60mmmin -1 ]]> 925.86 37.65 C3 <![CDATA[60mmmin -1 / 60mmmin -1 ]]> 798.59 30.09

[0091] From the results in Table 4, it can be seen that during the pulling process, the immersion speed of the flat support is: 180 mm min -1, pulling speed: 60mm min -1 When , the synthesized ZIF-8 / PMPS mixed matrix membrane has the highest pervaporation performance.

[0092] 9. Investigate the influence of the number of pulling times on the film during the pulling process

[0093] The effects of different immersion-pulling times in the casting solution on the performance of 14 nm-ZIF-8 / PMPS mixed matrix membrane (ZIF-8 loading of 13.0 wt.%) were prepared according to the method in the previous "a". The mass ratio of catalyst / crosslinker / polymer / ZIF-8 / solvent in the casting solution was 1:10:100:15:800, the residence time in the casting solution was 10 s, and the immersion speed was 180 mm min -1 , pulling speed: 60mm min -1 The prepared mixed matrix membrane was subjected to pervaporation test in a 1 wt.% n-butanol / water solution at 40°C. The results are shown in Table 5:

[0094] Table 5

[0095] Product Number Dipping-pulling times <![CDATA[Flux (gm -2 h -1 )]]> <![CDATA[n-BuOH / H2O separation factor]]> D1 1 925.86 37.65 D2 2 505.86 38.95 D3 3 334.87 39.09

[0096] From the results in Table 5, it can be seen that the ZIF-8 / PMPS mixed matrix membrane synthesized has the highest pervaporation performance when the impregnation-pulling process is performed once in total. If the impregnation-pulling process is repeated 2 or 3 times, the performance of the membrane decreases due to the thickening of the membrane layer.

[0097] Example 2 Performance of mixed matrix membrane pervaporation for butanol enrichment in the temperature range of 40-80°C

[0098] The performance of the mixed matrix membrane in pervaporation enrichment of butanol in the temperature range of 40 to 80° C. was investigated by taking the 14nm-ZIF-8 / PMPS mixed matrix membrane with a 13wt.% 14nm-ZIF-8 loading prepared in Example 1. The operating temperature was tested with a temperature increase trend. After each operating temperature test, the temperature of the water bath was adjusted until the temperature of the raw material solution (1.0wt.% n-butanol / water solution) reached the target temperature. A 20-min pre-pumping process was performed before the test at the target operating temperature. After the pre-pumping, the pervaporated permeate was officially collected for flux calculation and component analysis using chromatography to calculate the selectivity at this operating temperature.

[0099] As attached Figure 4As shown in the figure, during the pervaporation test, the operating temperature was set at 40℃, 50℃, 60℃, 70℃, and 80℃. The total permeation flux of the mixed matrix membrane increased significantly with the increase of the pervaporation feed liquid temperature, and the n-BuOH / H2O separation factor also increased with the increase of temperature. When the temperature increased from 40℃ to 80℃, the pervaporation flux increased from 744.06 gm - 2 h -1 Increased to 2356.85gm -2 h -1 , the n-BuOH / H2O separation factor increased to 43.27.

[0100] Example 3: Investigating the performance of mixed matrix membranes with different feed solution concentrations in pervaporation enrichment of butanol

[0101] The 14nm-ZIF-8 / PMPS mixed matrix membrane with a 13wt.% 14nm-ZIF-8 loading prepared in Example 1 was used to investigate the pervaporation performance of different concentrations of raw liquid at 40°C. After each raw liquid concentration test, the raw liquid concentration was adjusted to the target concentration, and a 20-min pre-pumping process was performed before testing at the target raw liquid concentration. After the pre-pumping, the pervaporated permeate was officially collected for flux calculation and component analysis using chromatography to calculate the selectivity at this raw liquid concentration.

[0102] As attached Figure 5 As shown in the figure, during the pervaporation test, the concentration of n-butanol / water system was set to 0.1wt.%, 0.5wt.%, 1.0wt.%, 2.0wt.%, 2.5wt.%, and 3.0wt.%, and the total permeation flux of the ZIF-8 / PMPS mixed matrix membrane increased with the increase of the concentration of the pervaporation feed solution. With the continuous increase of the n-butanol content in the feed solution, the total permeation flux increased from 625.20 g·m -2 ·h -1 Increased to 1272.33 g·m -2 ·h -1 , the n-BuOH / H2O separation factor also fluctuates in the range of 33.07 to 38.17.

[0103] Example 4: Investigation of the long-term stability of ZIF-8 / PMPS mixed matrix membranes

[0104] This example investigates the long-term stability of the 14nm-ZIF-8 / PMPS mixed matrix membrane prepared in Example 1 with a 13wt.% 14nm-ZIF-8 loading in a 1wt.% n-butanol / water system at 40°C. Figure 6 As shown in the figure, the stability test lasted for 600 hours and the average flux was 872.19 g·m -2 ·h -1The average selectivity is 35.83, indicating that the mixed matrix membrane has good long-term stability in the n-butanol separation system.

[0105] Example 5: Magnification Experiment

[0106] A flat support with a length × width of 10 cm × 10 cm (thickness of 6 mm) was used to prepare a mixed matrix flat membrane (ZIF-8 loading of 13 wt.%) according to the method of "I" in Example 1. The pervaporation performance of a 1 wt.% n-butanol / water solution at 40°C was tested. The flux of the 10 cm × 10 cm mixed matrix flat membrane was 728.40 gm -2 h -1 The n-BuOH / H2O separation factor is 19.09, indicating that a flat membrane that can be used in industry can be successfully prepared after scale-up.

[0107] The membrane preparation process in the prior art is difficult to scale up, and the performance of the membrane prepared by scaled-up production often does not meet the standard, and the membrane cannot be evenly and effectively loaded on the support, resulting in the membrane having a very low n-BuOH / H2O separation factor or even no separation performance. Compared with the prior art, the process of the present invention can not only ensure the high selectivity of the mixed matrix membrane while improving the permeability of the membrane, but also can still prepare qualified products when scaled-up production is carried out, and is suitable for industrial-scale production and promotion.

Claims

1. A method for preparing a hydrophobic MOF material mixed matrix flat membrane, characterized in that: The steps include: S1. Prepare liquid A: weigh MOF material and cross-linking agent, add them into solvent, mix them thoroughly, and obtain liquid A; S2. Prepare liquid B: weigh the organic polymer, add the solvent, and mix thoroughly to obtain liquid B; S3, preparing a casting solution: mixing liquid A with liquid B, mixing them thoroughly and evenly, adding a catalyst, and mixing them evenly to obtain a casting solution; S4. Preparation of mixed matrix flat membrane The flat support is installed on a lifting machine, and the casting liquid is loaded onto the flat support by an immersion lifting process, and then dried to obtain a mixed matrix flat membrane.

2. The preparation method according to claim 1, characterized in that: The solvent is selected from one or more of methanol, ethanol, isooctane, n-heptane, and cyclohexane, preferably isooctane; The MOF material is selected from ZIF-8, ZIF-L, ZIF-67, ZIF-90, ZIF-7, and ZIF-71, preferably ZIF-8, and preferably the particle size of ZIF-8 is 10 to 120 nm or 14 to 50 nm; The organic polymer is selected from polymethylphenylsiloxane (PMPS), polydimethylsiloxane (PDMS), polyether block amide (PEBA), preferably polymethylphenylsiloxane (PMPS); The cross-linking agent is selected from tetraethyl orthosilicate (TEOS), methyl orthosilicate (TMOS), methyltrimethoxysilane (MTMS), preferably tetraethyl orthosilicate (TEOS); The catalyst is selected from dibutyltin dilaurate (DBTDL), dimethylcyclohexylamine (DMCHA), N,N-dimethylbenzylamine (DMBA), triethylenediamine (TEDA), preferably dibutyltin dilaurate (DBTDL); The flat support is selected from one of an α-Al2O3 carrier, a γ-Al2O3 carrier, a PAN carrier, and a PVDF carrier, and is preferably an α-Al2O3 carrier.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the catalyst, the cross-linking agent, the organic polymer, the MOF material and the solvent in the casting solution in step S3 is 1:(8-12):(90-110):(5-20):(300-1000), preferably 1:(8-12):(90-110):(5-16):(600-1000) or 1:(9-11):(95-105):(10-15):(800-1000) or 1:10:100:15:800; In step S4, the viscosity of the casting solution is 40 cP to 65 cP or 40 cP to 50 cP.

4. The preparation method according to claim 1, characterized in that: Step S1 specifically comprises: first weighing MOF material and adding it to a solvent (preferably by ultrasonic stirring and mixing) to prepare a MOF dispersion, adding a crosslinking agent and a solvent to the MOF dispersion, and mixing them thoroughly to obtain a liquid A; preferably, after adding the crosslinking agent and the solvent to the MOF dispersion, ultrasonic mixing and magnetic stirring are used to mix; Preferably, probe ultrasound is used, with an amplitude of 30% to 90% and a duration of 1 to 5 minutes, more preferably an amplitude of 60% and a duration of 5 minutes; The stirring rate of the magnetic stirring is 200-600 rpm, and the stirring time is 0.5-1 h, preferably the stirring rate is 600 rpm, and the stirring time is 1 h.

5. The preparation method according to claim 1, characterized in that: In step S2, the organic polymer is weighed and added to the solvent, and the mixture is mixed by magnetic stirring to obtain a liquid B; The stirring rate of the magnetic stirring is 200-600 rpm, and the stirring time is 0.5-1 h, preferably the stirring rate is 600 rpm, and the stirring time is 1 h.

6. The preparation method according to claim 1, characterized in that: In step S3, liquid A and liquid B are mixed, and ultrasonic and magnetic stirring are used to fully mix them, and then a catalyst is added and mixed to obtain a casting liquid; Preferably, probe ultrasound is used, with an amplitude of 30% to 90% and a duration of 1 to 5 minutes, more preferably an amplitude of 60% and a duration of 5 minutes; The stirring rate of the magnetic stirring is 200-600 rpm, and the stirring time is 0.5-1 h, preferably the stirring rate is 600 rpm, and the stirring time is 1 h.

7. The preparation method according to claim 1, characterized in that: In step S4, the immersion and pulling process is as follows: the support body is immersed in the casting liquid at a speed of 60 to 200 mm min -1 (Preferably 100~180mm min -1 Or 150~180mm min -1 ), the residence time is 5 to 30 s (preferably 5 to 25 s or 5 to 20 s or 5 to 10 s), and then the support is pulled out from the casting liquid at a pulling speed of 60 to 200 mm min -1 (Preferably 100-180 mmmin -1 Or 150~180mm min -1 ), the immersion-pulling operation is performed once or twice (preferably once); further preferably, the speed at which the support is immersed in the casting solution is 180 mm min -1 The residence time is 10s, and then the support is pulled out from the casting liquid at a pulling speed of 60mm min -1 ; The drying comprises air-drying the support with the casting liquid adhered to the surface and then drying it; preferably, drying at room temperature for 12 to 24 hours, then drying with air at 80 to 120°C for 6 to 12 hours, and finally drying in a vacuum at 80 to 120°C for 6 to 12 hours; further preferably, drying at room temperature for 24 hours, drying with air at 100°C for 12 hours, and drying in a vacuum at 100°C for 12 hours.

8. A mixed matrix flat membrane based on a hydrophobic MOF material, characterized in that: The preparation method is described in any one of claims 1 to 7.

9. Use of the mixed matrix flat membrane based on the hydrophobic MOF material as claimed in claim 8 in alcohol enrichment.

10. The use according to claim 9, characterized in that: Mixed matrix flat membranes are used to separate and enrich alcohols in pervaporation technology; The alcohols include n-butanol, isobutanol, n-propanol, isopropanol and ethanol; Preferably, the alcohol is n-butanol with a concentration of 0.1 to 3 wt % and an enrichment temperature of 40 to 80°C.

Citation Information

Patent Citations

  • Method for preparing organic / inorganic alcohol-permselective pervaporation composite membrane

    CN103182251A

  • Preparation method of high dispersion metal-organic framework (MOF) / organic hybrid priority alcohol through composite membrane

    CN104001426A

  • Mixed matrix membrane of bead-like MOF filled silicone rubber

    CN112316741A

  • Two-dimensional porous frame-based mixed matrix membrane as well as preparation method and separation application thereof

    CN118079661A

  • Method for preparing hierarchical structure UiO-66 material by hard template method, and preparation method and application of MOF-organic polymer mixed matrix membrane

    CN118165356A

Cited By

  • Hydraulic support surface treatment process

    CN120866900A